Palmitic Acid-BSA enhances Amyloid-β production through GPR40-mediated dual pathways in neuronal cells: Involvement of the Akt/mTOR/HIF-1α and Akt/NF-κB pathways - Jeong Yeon Kim (Nature Portfolio, 2017)
Abstract The pathophysiological actions of fatty acids (FAs) on Alzheimer’s disease (AD), which are possibly mediated by genomic effects, are widely known; however, their non-genomic actions remain elusive. The aim of this study was to investigate the non-genomic mechanism of extra-cellular palmitic acid (PA) regulating beta-amyloid peptide (Aβ) production, which may provide a link between obesity and the occurrence of AD. In an obese mouse model, a high-fat diet (HFD) significantly increased the expression levels of APP and BACE1 as well as the AD pathology in the mouse brain. We further found that PA conjugated with bovine serum albumin (PA-BSA) increased the expression of APP and BACE1 and the production of Aβ through the G protein-coupled receptor 40 (GPR40) in SK-N-MC cells. PA-BSA coupling with GPR40 significantly induced Akt activation which is required for mTOR/p70S6K1-mediated HIF-1α expression and NF-κB phosphorylation facilitating the transcriptional activity of the APP and BACE1 genes. In addition, silencing of APP and BACE1 expression significantly decreased the production of Aβ in SK-N-MC cells treated with PA-BSA. In conclusion, these results show that extra-cellular PA coupled with GPR40 induces the expression of APP and BACE1 to facilitate Aβ production via the Akt-mTOR-HIF-1α and Akt-NF-κB pathways in SK-N-MC cells.